2020
DOI: 10.1136/bmj.m2516
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of serological tests for covid-19: systematic review and meta-analysis

Abstract: AbstractObjectiveTo determine the diagnostic accuracy of serological tests for coronavirus disease-2019 (covid-19).DesignSystematic review and meta-analysis.Data sourcesMedline, bioRxiv, and medRxiv from 1 January to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
601
3
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 735 publications
(671 citation statements)
references
References 63 publications
25
601
3
11
Order By: Relevance
“…The results of many studies showed that their global sensitivity, speci city, positive predictive value (PPV) and negative predictive value (NPV) were equivalent to the ELISA IgG/IgM or the CLIA IgG/IgM tests 44 . Similarly, to previous studies, we found accordance between the two analytical methods.…”
Section: Discussionmentioning
confidence: 99%
“…The results of many studies showed that their global sensitivity, speci city, positive predictive value (PPV) and negative predictive value (NPV) were equivalent to the ELISA IgG/IgM or the CLIA IgG/IgM tests 44 . Similarly, to previous studies, we found accordance between the two analytical methods.…”
Section: Discussionmentioning
confidence: 99%
“…In a linked paper, Bastos and colleagues (doi:10.1136/bmj.m2516) provide a much needed review of the performance of serological assays to accurately detect antibodies to SARS-CoV-2 2. They meta-analyzed 40 studies according to type of antibody test (enzyme linked immunosorbent assays (ELISAs), lateral flow immunoassays (LFIAs), and chemiluminescent immunoassays (CLIAs)), and for each type, determined the average or pooled sensitivity and specificity and assessed the studies for risk of bias.…”
Section: Not Good Enoughmentioning
confidence: 99%
“…Plasma collected from patients who have recovered from a SARS-CoV-2 infection can contain antiviral antibodies detectable through serological testing 2 . It is unclear to what extent these antibodies provide anti-viral protection, but at least a subset of patients presents with high titres of neutralizing antibodies, or with speci c potent antibodies irrespective of the titre 3 .…”
Section: Background and Rationale {6a}mentioning
confidence: 99%